Conditional Process Analysis of the Correlation Between Achievement Motivation and Performance - Ahmad Gunawan; Dadang Heri Kusumah (Management Studies and Entrepreneurship Journal (MSEJ), 2023)
The purpose of this study. To explore the relationship between achievement motivation and job performance, this study investigated the impact of different personality traits on job performance among employees. Method. This cross-sectional study is being conducted in 2023. The types of data collected include achievement motivation, job performance, organizational commitment, personality traits, and other demographic variables. To assess and compare demographic data, independent t-tests and ANOVA are applied. Next, the Pearson correlation coefficient is used to evaluate correlations among variables. Moderated mediation analyses were conducted to examine the correlation between job performance, achievement motivation, organizational commitment, neuroticism, extraversion, openness, agreeableness, and conscientiousness. Result. Achievement motivation directly affects job performance and organizational commitment partly mediates the direct effects of achievement motivation on job performance. In addition, our findings suggest that agreeableness and conscientiousness moderate the strength of the relationship between achievement motivation and work performance mediated by organizational commitment. Conclusion. We propose that hospital managers should pay attention to the personal growth of physicians and increase their organizational commitment through the creation of a positive work climate and training for career planning and education. In addition, managers must identify the conscientiousness and agreeableness of individuals and increase their responsibilities directed at improving organizational performance.